Formation of Fund of Printed Periodicals for Children and Youth in Soviet Society in 1920-30s - L. P. Malakhova (Научный диалог)
The ideological conditions and mechanisms of formation of the Fund of children’s publications in the 1920-30s are considered. The review of various types of historical sources and works of modern scientists on similar problems is carried out. The author analyzes the state policy in the sphere of formation of the common information space for children and teenagers through printed publications as more accessible and effective mass media. Particular attention is paid to the key positions in the texts of documents relating to the development of children’s books, magazines and newspapers. The state bodies implementing the party’s policy in the field of publications for children and youth are listed. The review of the themes of children’s books and periodicals is made, that allows to draw conclusions about the image of a new hero for Soviet children they create. The article raises the question of the content and fullness of library collections in the departments of children’s literature. The direction of library “purges” as the most important factor influencing the formation of information space of younger generation is analyzed. The interdisciplinary methodological approach allows to study objectively the process of acquisition of a universal fund of printed publications for children and teenagers, to analyze and systematically present the content of books and periodicals, to assess the educational potential of the formed information space.